Evaluating the RUSLE model and developing an empirical equation for estimating soil erodibility factor in a semi-arid region - Vaezi, A. R.; Sadeghi, S. H. R. (Spanish Journal of Agricultural Research, 2011)
<span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Soil erodibility is one of six factors in the revised universal soil loss equation (RUSLE) that reflects the ease with which the soil is detached by splash during rainfall and/or by surface flow. This study was therefore carried out to assess applicability of the RUSLE model in estimating erodibility factor (<span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">K<span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">) and develop an appropriate equation to predict this factor in soils of the semi-arid region in Iran. Thirty six dry-farming lands were considered in a 900 km<span style="font-size: 6pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">2 <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">agricultural zone in Hashtroud, northwest of the country. Soil loss was measured at 108 unit plots under natural rainfall events for a 2-year period from March 2005 to March 2007. The <span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">K<span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">-factor was estimated using the mean geometric diameter of soil particles (<span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">D<span style="font-size: 6pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">g<span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">) and measured based on the mean annual soil loss per unit rainfall-runoff erosivity factor (<span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">R<span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">). Based on the results, the estimated <span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">K <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">values varied from 0.0316 and 0.0485 t h MJ<span style="font-size: 6pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">–1 <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">mm<span style="font-size: 6pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">–1 <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">and the measured <span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">K <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">values were ranged from 0.0014 to 0.0050 t h MJ<span style="font-size: 6pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">–1 <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">mm<span style="font-size: 6pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">–1<span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">. The measured <span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">K <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">values were almost 14 fold smaller than the estimated values on average. There was no considerable correlation between the measured <span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">K<span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">-factor and <span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Dg <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">(<span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">R<span style="font-size: 6pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">2 <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">= 0.05). Multi-regression analysis showed that the measured <span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">K<span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">-factor was significantly related to the aggregate stability and permeability (<span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">R<span style="font-size: 6pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">2<span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">= 0.90, <span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">p <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">< 0.001). Although <span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">D<span style="font-size: 6pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">g <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">was positively correlated with the soil permeability (<span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">R<span style="font-size: 6pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">2 <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">= 0.42), it did not strongly affect the measured K-factor (<span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">R<span style="font-size: 6pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">2 <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">= 0.05) because of its negative effect on aggregate stability (<span style="font-size: 10pt; font-family: ’Calibri’,’sans-serif’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">R<span style="font-size: 6pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">2 <span style="font-size: 10pt; font-family: ’TimesNewRomanPS’,’serif’; mso-bidi-font-family: TimesNewRomanPS; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">= 0.64)